Continuous thermosalinograph oceanography along Heincke cruise HE561 - Bernadette Pogoda; Gerd Rohardt (PANGAEA, 2021)
Data obtained by a thermosalinograph (SBE21, SeaBird GmbH) and an external temperature sensor (SBE38, Sea-Bird GmbH) were processed to receive a validated data set of temperature and salinity on board RV Heincke during cruise HE561. Unvalidated data of conductivity sensor, internal and external temperature are extracted from the DAVIS SHIP data base (https://dship.awi.de) in a 1-second interval. The salinity was calculated using conductivity and internal temperature by applying the Practical Salinity Scale 1978 (PSS-78). After applying different filters, processed data are provided as 5min means of salinity and water temperature aligned with position data taken from master track of the respective cruise. For further details see the processing reports of each cruise.